1997
DOI: 10.1023/a:1018377621102
|View full text |Cite
|
Sign up to set email alerts
|

Lipid hydroperoxide-induced tumor necrosis factor (TNF)- , vascular endothelial growth factor and neovascularization in the rabbit cornea: effect of TNF inhibition

Abstract: Lipid hydroperoxides (LHP) at high concentrations are cytotoxic, but at sublethal concentration, they induce synthesis of cytokine vascular growth factors. Intracorneal injections of 30 μg LHP placed 5 mm from the superior limbus stimulated early vasodilation of limbal vasculature and a rapidly developing, sustained neovascularization. Under these conditions, vessels grew at the rate of 0.3 mm/day to a total length of 7.5 mm, 25 days after injection. Cholesterol peroxides were less effective. Developing vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
1
20
1
Order By: Relevance
“…Similarly, our data show that above 10-5 M, 18:2-OOH, a product of oxidative reactions, is cytotoxic but at sub-lethal levels can induce neovascularization. A similar result was obtained in the retina and cornea of albino rabbits [6]. Lipid peroxy radicals are formed by the decomposition of LHP in the presence of ferric iron or cupric iron [25].…”
Section: Effect Of 18:2-ooh and Antioxidants On Bfofsupporting
confidence: 81%
See 2 more Smart Citations
“…Similarly, our data show that above 10-5 M, 18:2-OOH, a product of oxidative reactions, is cytotoxic but at sub-lethal levels can induce neovascularization. A similar result was obtained in the retina and cornea of albino rabbits [6]. Lipid peroxy radicals are formed by the decomposition of LHP in the presence of ferric iron or cupric iron [25].…”
Section: Effect Of 18:2-ooh and Antioxidants On Bfofsupporting
confidence: 81%
“…In contrast, the bFGF concentration in the presence of 10-' M 18:2-OOH was increased to 3.8± 1.7 pg/mg protein after 1 h and to 5. of LHP stimulated neovascularization, and LHP appeared to mediate the vascular process in a dose-dependent manner by increasing the concentrations of both VEGF and TNF-a at picomole threshold levels [6]. We could not detect VEGF or TNF-a in the present culture medium.…”
Section: Effect Of 18:2-ooh and Antioxidants On Bfofcontrasting
confidence: 55%
See 1 more Smart Citation
“…Decreased expression of vWF and ·-SMA is consistent with reduced expression of the important angiogenic factors, angiogenin and VEGF. TNF-· is known to be pro-angiogenic in vivo, despite its reported anti-angiogenic properties in vitro (27,28). Down-regulation of VEGF has also been observed following administration of several angiogenesis inhibitors, including recombinant PK1-3 (26), plasminogen kringle 5 (PK5) (29) and apolipoprotein kringles (14), and also following adenoviral vector delivery of angiostatin and endostatin (30).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that LHP induces neovascularizaion (NV) in a New Zealand albino rabbit corneal model (21,22) through upregulation of particular cytokines, especially tumor necrosis factor-alpha (TNF-α) and VEGF. The NV response was enhanced by hyperglycemic conditions (23), and it was suppressed by vitamin E treatment (24).…”
Section: Introductionmentioning
confidence: 99%